FRI0364 Does An Elevated Serum Immunoglobulin A Level Predict The Course of Adult IGA Vasculitis?. (15th July 2016) - Hočevar, A.; Ostrovršnik, J.; Rotar, Ž.; Tomšič, M.
Abstract : Objectives: Our objective was to evaluate the impact of serum IgA level on the clinical presentation and severity of adult IgA vasculitis (IgAV). Methods: We prospectively collected data on newly diagnosed histologically proven adult IgAV cases between January 2013 and December 2015 at our at our secondary/tertiary rheumatology centre. Patients were stratified according to the serum level of IgA into two groups (elevated IgA (>4.10 g/l) vs. normal IgA (0.7–4.10 g/l)). Results: During the 36 month observation period, 92 new adult IgAV cases (54% male) were identified. The median age was 65.8 (interquartile range (IQR) 48.7–77.3, range 19–88) years and the median disease duration (IQR, range) 7 (6–21, 2–120) days. The serum level of IgA was elevated in 39 (42.4%) cases. The characteristics of IgAV groups with increased and with normal serum IgA level at presentation and at follow-up are presented in Table 1 . Follow-up data were available for 59 (24 had elevated IgA) patients, with a median (IQR) follow-up of 7.2 (5.0–14.5) months. Conclusions: Elevated IgA serum level does not seem to have any significant impact on the disease manifestations and severity of adult IgAV. However, there was a trend toward less frequent antecedent infections and more frequent malignancy development in the group with high serum IgA. Disclosure of Interest: None declared